Large amounts of marine debris found in sperm whales stranded along the North Sea coast in early 2016. Issue 1 (15th November 2016) - Unger, Bianca; Rebolledo, Elisa L. Bravo; Deaville, Rob; Gröne, Andrea; IJsseldijk, Lonneke L.; Leopold, Mardik F.; Siebert, Ursula; Spitz, Jérôme; Wohlsein, Peter; Herr, Helena
Abstract: 30 sperm whales ( Physeter macrocephalus ) stranded along the coasts of the North Sea between January and February 2016. The gastro-intestinal tracts of 22 of the carcasses were investigated. Marine debris including netting, ropes, foils, packaging material and a part of a car were found in nine of the 22 individuals. Here we provide details about the findings and consequences for the animals. While none of the items was responsible for the death of the animal, the findings demonstrate the high level of exposure to marine debris and associated risks for large predators, such as the sperm whale. Highlights: Stranded sperm whales had large amounts of marine debris in their stomachs Up to 25 kg of debris were collected from a single animal Fishing related debris represented a high proportion of the findings. General litter consisted of items of daily use (coffee capsule, chocolate wrappings) Findings demonstrate the risks associated with the ingestion of marine debris